A-Z of nutritional supplements: dietary supplements, sports nutrition foods and ergogenic aids for health and performance: Part 45 - Godfrey, R. J.; Laupheimer, M. W.; Stear, S. J.; Burke, L. M.; Castell, L. M. (British Journal of Sports Medicine, 2013)
Part 45 contains a trio of topics beginning with `Y`. Yerba maté, a fairly well-known herbal tea, contains caffeine, which accounts for its association with sports performance. Yohimbine, an alkaloid, has traditionally been used as a herbal preparation to combat erectile dysfunction. However, more recently, claims have been made for its putative role in bodybuilding. Yucca, a family of 40-50 shrubs and trees, is marketed as having anti-inflammatory and antiarthritic properties.